The response strategies to saline-alkali stress in wheat: Soil improvement, agronomic management, salt-tolerant variety breeding, and biochemical regulation - Wang, Xiaobing; Li, Xiaoyu; Dai, Yabo (Geographical Research Bulletin, 2025)
Wheat saline-alkali stress is one of the major challenges facing global agriculture, particularly in arid and semi-arid regions, significantly affecting crop growth, yield, and quality. Researchers have conducted in-depth studies in four key areas to enhance wheat salt tolerance and achieve sustainable agriculture. In soil improvement, microbial remediation techniques, novel soil amendments, and smart agricultural technologies effectively enhance soil conditions. Agronomic management practices, such as precise water and fertilizer management, optimized crop rotation and intercropping systems, and plant signal molecule regulation, improve wheat growth conditions. Salt-tolerant variety breeding, supported by genomics, gene editing, and phenomics, accelerates the identification and application of salt-tolerant genes. Biological and chemical regulation approaches, including the utilization of rhizosphere microbes, exogenous regulatory substances, and RNA-based mechanisms, provide critical support for improving wheat salt tolerance. In the future, integrating interdisciplinary technologies with precision management strategies is expected to enhance wheat resistance to saline-alkali stress further and unlock the agricultural potential of saline-alkali lands.